2017
DOI: 10.3390/geosciences7030057
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biofilms upon Surfaces Relevant to an Intermediate Level Radioactive Waste Geological Disposal Facility under Simulated Near-Field Conditions

Abstract: Abstract:The ability of biofilms to form on a range of materials (cementious backfill (Nirex Reference Vault Backfill (NRVB)), graphite, and stainless steel) relevant to potential UK intermediate level radioactive waste (ILW) disposal concepts was investigated by exposing these surfaces to alkaliphilic flocs generated by mature biofilm communities. Flocs are aggregates of biofilm material that are able to act as a transport vector for the propagation of biofilms. In systems where biofilm formation was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…The generation of eDNA is often associated with biofilm formation, in which it provides both a scaffold material as well as a potential source of nutrients 29 , 30 . In this study the eDNA formed the basal layer of the biofilm at both pH values, as previously observed at alkaline pH on virgin graphite 21 . This suggests that the simulated surface deposits investigated here did not alter biofilm initiation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The generation of eDNA is often associated with biofilm formation, in which it provides both a scaffold material as well as a potential source of nutrients 29 , 30 . In this study the eDNA formed the basal layer of the biofilm at both pH values, as previously observed at alkaline pH on virgin graphite 21 . This suggests that the simulated surface deposits investigated here did not alter biofilm initiation.…”
Section: Discussionsupporting
confidence: 83%
“…showed that emplaced cotton cellulose within a highly alkaline site provided not only a substrate for CDP generation, but also a surface on which biofilm could form, allowing a flocculate-forming CDP-degrading community to be sub-cultured 16 . These flocs have been shown to provide protection against alkaline pH values by creating internal low pH environments 20 and be able to facilitate biofilm formation on cementitious backfill material and a range of surfaces relevant to potential UK ILW disposal concepts 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation allows microorganisms to control their immediate environment by generating physical and chemical gradients at the micron scale. This control may lead to ecological advantages including protection against external stressors (Davey & O'Toole, 2000) such as antibiotics (Hall & Mah, 2017), disinfectants (Muazu et al, 2017), and pH (Charles, Rout, Laws, et al, 2017). Through global industrial activity and the prevalence of acid mine drainage, acidophiles and acidophilic biofilms have received considerable research focus (Aliaga Goltsman et al, 2015; Huang et al, 2016; Jiao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Flocculants (flocs) are a type of biofilm that is typically a free‐floating composite of biofilm material and microbial cells. These flocs survived by using the extracellular polymeric substance (EPS) to attenuate the internal pH experienced by the resident microbial community (Charles, Rout, Laws, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies showed that microbes can survive and even thrive under the hyperalkaline conditions that are expected in a cementitious GDF by forming flocks and biofilms that shield them from the high pH (Charles et al . 2015 , 2017a , b , 2019 ). Microbes have been found recently to bloom in high doses of ionising radiation in a high-pH outdoor spent nuclear fuel storage pond at Sellafield, UK (Foster et al .…”
Section: Introductionmentioning
confidence: 99%